"Primary Omental Hydatid Cyst": A Rare Entity. (23rd September 2012) - Sable, Shailesh; Mehta, Jyoti; Yadav, Sudeep; Jategaokar, Priyadarshan; Haldar, Premashish J.
Abstract : Hydatid cyst is caused by the parasite Echinococcus granulosus commonly seen in temperate regions. Primary omental hydatid cyst is rare entity. Diagnosis can be achieved with contrast-enhanced computed tomography of abdomen and pelvis along with serology. Eosinophilia is a strong pointer to hydatid cyst as a differential diagnosis. Open or laparoscopic excision of the cyst along with medical therapy remains the treatment of choice.